Russia's energy sector between politics and business - Orttung, Robert; Perovic, Jeronim; Pleines, Heiko; Schröder, Hans-Henning; Forschungsstelle Osteuropa an der Universität Bremen (DEU, 2015)
Contents: Jeronim Perovic, Robert Orttung: Russia's energy policy: should Europe worry? Russian oil and gas production. Russia's oil and gas industry in an international context (7-26). Part I Russia's energy policy: economic challenges and political strategies - Daniel Simmons, Isabel Murray: Russian gas: will there be enough investment? (27-30); Julia Kusznir, Heiko Pleines: The Russian oil industry between foreign investment and domestic interests. FDI and state ownership in the oil and gas industry (31-35); Susanne Wengle: Power politics: electricity sector reforms in post-Soviet Russia. Attitudes of the Russian public towards the privatization of UES (41-44). Part II Russia's new energy frontiers - Indra Overland: Shtokman and Russia's Arctic petroleum frontier (45-49); Nina Poussenkova: All quiet on the eastern front. (50-55); Elana Wilson Rowe: Regional influence in oil and gas development: a case study of Sakhalin (56-62). Part III Energy and foreign policy - Jeronim Perovic: Russian energy power abroad (63-66); Andreas Heinrich: Gazprom's expansion strategy in Europe and the liberalization of EU energy markets. Gazprom joint ventures, EU gas imports (67-74); Matteo Fachinotti: Will Russia create a gas cartel? (75-78); Yoshinori Takeda: Russia's new political leadership and its implication for East Siberian development and energy cooperation with North East Asian states (79-84). Part IV Ecological challenges - Roland Götz: Russia and global warming - implications for the energy industry (85-88); Petra Opitz: Energy savings in Russia - political challenges and economic potential. Russian CO2 emissions and energy consumption in international perspective (89-96).